The Adipocyte as a Novel TSH Target - Sorisky, A.; Antunes, T. T.; Gagnon, A. (Mini Reviews in Medicinal Chemistry, 2008)
Thyroid stimulating hormone (TSH; also known as thyrotropin), binds cognate receptors on the surface of thyrocytes to regulate proliferation and thyroid hormone synthesis. This unidimensional view of TSH is being transformed as new evidence indicates that TSH acts on adipose tissue. Adipocyte inflammatory responses that predispose to cardiovascular disease may occur in thyroid disorders associated with elevated TSH levels.
Keywords: adipocyte